(Auto)biographic Discourse in A.S. Khomyakovʼs Epistolary - Marina D. Kuzmina (Studia Litterarum)
The article discusses autobiographical and biographical discourse in the epistolary of A.S. Khomyakov. It turns out that both, and especially the former, are underrepresented. Khomyakov steadily replaces autobiographical elements typical of the epistolary genre and thereby expected by the reader with biographical elements, almost always in the form of obituary. As a rule, those are obituaries to public figures who had left a mark in history, influenced contemporaries, and possibly descendants — what mostly interests Khomyakov as the author. Paying primary attention to personal qualities, the scope and degree of self-realization of these qualities, he almost never covers external, factual side of their lives. Thus, the epistolary includes, on the one hand, paradoxical elements of the obituary and the biographical genre without a typical biographic narrative, while on the other hand, a highly individualized version of the obituary, a genre that, at a time, seemed to have hopelessly exhausted itself and become clichéd.